2022
DOI: 10.1108/ijmce-12-2021-0114
|View full text |Cite
|
Sign up to set email alerts
|

Coaching and teaching performance in higher education: a literature review

Abstract: PurposeThe purpose of this literature review was to identify best practices in coaching faculty within higher education and the subsequent benefits of effective faculty coaching programs for the retention of quality faculty. In higher education, where an emphasis is on the delivery of curriculum for student learning, faculty performance reviews are not universally defined, nor are coaching practices consistently employed. Giving teaching performance feedback promptly to faculty may be a means to foster profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The instructional quality of university education is a major concern for policy makers, administrators and international accreditation organizations (Alfraih and Alanezi, 2016; Burleigh et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instructional quality of university education is a major concern for policy makers, administrators and international accreditation organizations (Alfraih and Alanezi, 2016; Burleigh et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The instructional quality of university education is a major concern for policy makers, administrators and international accreditation organizations (Alfraih and Alanezi, 2016;Burleigh et al, 2023). For example, Kaur and Bhalla (2018) reported that professorial effectiveness is amongst the most important factors governing the provision of high-quality education.…”
Section: Introductionmentioning
confidence: 99%